System Dynamic Modeling in Blood Supply System (Case Study) - Eva Oktaviana; Andriansyah; Raihan Dara Lufika; Nissa Prasanti (School of Industrial and System Engineering, Telkom University, 2021)
XYZ is one of the agencies that handle the distribution of blood with the amount of supply needed to meetdemand is uncertain. Problems occur in inventory management which has an impact on bloodstockfluctuations. This research was conducted using a dynamic system approach to design a blood supplymodel at XYZ and provide recommendations for the best scenario for existing problems based on thepriority indicators of the objectives. The structure of the model is described in causal loop diagrams andstock and flow diagrams. The objective function of this modeling model is to minimize the instability ofthe blood supply so that it can stabilize the intake and output of blood donors. Four policy scenarios aresimulated in the model with the parameters used is the number of replacement donors and low expiredblood. The simulation result for the best scenario is a scenario that has 230 donor bags every 15 days witha policy of procuring donors twice in one month.